Vascular complications of amebic liver abscess – Computed tomography case series with review of the literature - Bhavna Arora; Lovleen Kakkar; Sachin Mahal (Turkish Journal of Emergency Medicine, 2025)
Amebiasis is a parasitic infection with amebic liver abscess (ALA) being the most common extraintestinal manifestation. Common complications of ALA include rupture into the pleural, pericardial, or peritoneal cavity. Uncommonly, they can cause vascular complications such as thrombosis of the hepatic vein and inferior vena cava which may further extend to the right atrium or may embolize resulting in pulmonary thromboembolism. In this study, we report three patients with vascular complications in ALA. The presence of vascular pathology in ALAs should not be missed. With its detection and prompt treatment, the progression of vascular complications can be prevented.